LABOR MARKET PROBLEMS AND EMPLOYMENT OPPORTUNITIES FOR SEVERELY WOUNDED COMBATANTS (Psychology Travelogs, 2025)
The article examines the current labor market problems faced by severely wounded combatants, as well as the possibilities of their employment in the context of modern Ukraine. The main focus is on the issues of reintegration of veterans into social life and the labor market, as well as the importance of intersectoral cooperation to ensure effective support for this social group.The analysis of statistical data, in particular from the Ministry of Veterans Affairs of Ukraine and the State Employment Center, shows an increase in the number of unemployed combat veterans. The study emphasizes that underestimating the depth of reintegration problems, especially for severely wounded combatants, can lead to negative social and economic consequences.The paper identifies the challenges faced by veterans, outlining the physical, psychological, and social barriers that complicate their adaptation. The role of government programs, NGOs, and social entrepreneurship in providing opportunities for retraining, psychological rehabilitation, and employment for veterans is considered.Particular attention is paid to the prospects of remote work and mastering digital professions, which are becoming an important area of support for people with disabilities. The article outlines the main areas and opportunities for employment of severely wounded combatants, emphasizing the importance of a comprehensive approach to solving these problems.The results of the study emphasize the need to develop effective mechanisms for adaptation, retraining and social support aimed at reintegrating severely wounded combatants into the labor market. The author emphasizes that only close cooperation between state institutions, employers and public organizations will be able to provide decent conditions for veterans, contributing to their well-being and strengthening the country’s socio-economic stability.
Keywords: reintegration; employment; veterans; combatants; adaptation; support